The clinical characteristics and risk factors for severe COVID-19 in patients with COVID-19 and tuberculosis coinfection - Wang, Yang; Chen, Yanping; Gu, Lina; Lou, Lixin; Zhang, Jian; Zhang, Kaiyu (Frontiers in Microbiology, 2022)
Background Under the wave of the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) variant Omicron epidemic, the number of infectious cases has increased dramatically in Jilin Province, China since March 2022.The clinical features and severity of SARS-CoV-2 Omicron variant infection in tuberculosis (TB) patients are not yet clear. Methods Data were obtained from 153 patients with the Omicron variant and TB coinfection and 153 non-TB COVID-19 patients who had been hospitalized at Changchun Infectious Disease Hospital from March to June 2022. Results Among these coinfection patients, 17 patients showed COVID-19-related pneumonia on chest imaging and 11 were diagnosed with severe COVID-19. The median duration of SARS-CoV-2 clearance was 13 days. The negative conversion time was associated with age, COVID-19-related pneumonia and antibody IgG. A higher white blood cell count, a lower lymphocyte percentage, a higher CRP level, and a higher D-dimer level were found in the severe group. Age and increased PCT were individual risk factors for the severity of COVID-19. Compared with the non-TB patients, the coinfection patients had higher severity of COVID-19 and the elder coinfection patients had a longer negative conversion time. Conclusion This study found an association between age, pneumonia, antibody IgG and RNA negative conversion time in COVID-19 and TB coinfection patients, and age and increased PCT were risk factors for the severity of COVID-19.